Influence of cortical bone thickness and implant length on implant stability at the time of surgery—clinical, prospective, biomechanical, and imaging study - Miyamoto, Ikuya; Tsuboi, Yoichi; Wada, Eishin; Suwa, Hirohiko; Iizuka, Tadahiko (Bone (New York, N.Y.), 2005)
This clinical study is the first to quantitatively evaluate both regional bone structure by computed tomography preoperatively and dental implant stability by resonance frequency analysis at the time of surgery to explore the relation between local bone structure and dental implant stability in humans. Implant stability at the time of installation is often difficult to achieve in lower density bone and implant stability might influence treatment efficacy. Few clinical studies have reported detailed bone characteristics obtained using computed tomography prior to surgery and comprehensive implant stability measurements at the time of surgery. We hypothesized that thicker cortical bone would improve the stability of the dental implant at the time of placement. Before radiographic examination, diagnostic radiographic templates were made by incorporating radiopaque indicators. Computed tomography scans were obtained for 50 edentulous subjects prior to surgery. Preoperatively, the thickness of the cortical bone at the sites of implant insertion was measured digitally, and then implant insertion surgery was performed. A total of 225-implant stability measurements were made using a resonance frequency analyzer. There was a strong linear correlation between cortical bone thickness and resonance frequency ( r = 0.84, P < 0.0001). The implant length had a weak negative correlation with stability ( r = −0.25, P < 0.0005). These results suggest that the initial stability at the time of implant installation is influenced more by cortical bone thickness than by implant length. The cortical and cancellous ratio of local bone is extremely important for implant stability at the time of surgery and determining the local bone condition is critical for treatment success.